Ultra‐High‐Frequency Algorithmic Arbitrage Across International Index Futures. (20th June 2014) - Alsayed, Hamad; McGroarty, Frank; Breitner, Michael H.; Dunis, Christian; von Mettenheim, Hans-Jörg; Neely, Christopher; Sermpinis, Georgios
ABSTRACT We show that persistent lead–lag relationships spanning mere fractions of a second exist in all three possible pairings of the S&P 500, FTSE 100 and DAX futures contracts. These relationships exhibit clear intraday patterns which help us to forecast mid‐quote changes in lagging contracts with directional accuracy in excess of 85%. A simple algorithmic trading strategy exploiting these relations yields economically significant profits which are robust to market impact costs and the bid–ask spread. We find that price slippage and infrastructure costs are our most important limits to arbitrage. Our results support the impossibility of EMH view that informational inefficiencies incentivize arbitrageurs to eliminate mispricings. Copyright © 2014 John Wiley & Sons, Ltd.